2022
DOI: 10.1097/gco.0000000000000779
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres, aging and reproduction

Abstract: Purpose of reviewWomen's fertility decay starts at the mid 30 s. However, the current delay of childbearing leads to ovarian aging and the need of assisted reproduction technologies (ART). Telomere biology is one of the main pathways involved in organismal aging. Thus, this review will focus on the knowledge acquired during the last 2 years about the telomere pathway and its influence on female fertility and the consequences for the newborn.Recent findingsNew research on telomere biology reaffirms the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…A reflection of aging processes is the final sequences of chromosomes, called telomeres. They are mainly responsible for chromosomes’ continued integrity and stability [ 53 , 54 ]. However, with each division, telomeres become shorter due to the shortening of descendant chromosomes within the telomeres and telomerase deficiency, until eventually the coding part of chromosomes is damaged [ 55 ].…”
Section: Sirt1 and Agingmentioning
confidence: 99%
“…A reflection of aging processes is the final sequences of chromosomes, called telomeres. They are mainly responsible for chromosomes’ continued integrity and stability [ 53 , 54 ]. However, with each division, telomeres become shorter due to the shortening of descendant chromosomes within the telomeres and telomerase deficiency, until eventually the coding part of chromosomes is damaged [ 55 ].…”
Section: Sirt1 and Agingmentioning
confidence: 99%
“…Partial subunit expression defects of the shelterin complex of CD4 + T cells in patients with BD suggest abnormal telomere status, loss of the original telomere protection of chromosomes, vulnerability to DNA damage and other attacks, and acceleration of cell aging and apoptosis ( 34 ). NF-kB signaling and exposure to inflammatory molecules, such as IL-6 or TNF, can regulate telomere length and activity ( 35 ). Studies have shown that telomere shortening and abnormal telomerase activity are closely related to autoimmune diseases like rheumatoid arthritis and systemic lupus erythematosus ( 36 39 ).…”
Section: T Cell Senescencementioning
confidence: 99%
“…In addition, the telomere theory is one of the latest mechanisms to explain female reproductive aging ( 147 ).Telomeres are nucleoprotein complexes at the end of chromosomes, maintaining the integrity of chromosomes and inhibit DNA damage reactions at the free end of chromosomes ( 148 ). It is widely recognized that telomeres are susceptible to oxidative damage, and OS markers have been shown to exhibit a negative correlation with telomere length ( 149 ).…”
Section: Mitochondrial Dysfunction Leads To Ovarian Agingmentioning
confidence: 99%